Reliability and criterion-related validity of a new repeated agility test - Fessi, MS; Makni, E; Jemni, M; Elloumi, M; Chamari, K; Nabli, MA; Padulo, J; Moalla, W (Biology of Sport, 2016)
The study aimed to assess the reliability and the criterion-related validity of a new repeated sprint T-test (RSTT) that includes intense multidirectional intermittent efforts. The RSTT consisted of 7 maximal repeated executions of the agility T-test with 25 s of passive recovery rest in between. Forty-five team sports players performed two RSTTs separated by 3 days to assess the reliability of best time (BT) and total time (TT) of the RSTT. The intra-class correlation coefficient analysis revealed a high relative reliability between test and retest for BT and TT (>0.90). The standard error of measurement (<0.50) showed that the RSTT has a good absolute reliability. The minimal detectable change values for BT and TT related to the RSTT were 0.09 s and 0.58 s, respectively. To check the criterion-related validity of the RSTT, players performed a repeated linear sprint (RLS) and a repeated sprint with changes of direction (RSCD). Significant correlations between the BT and TT of the RLS, RSCD and RSTT were observed (p<0.001). The RSTT is, therefore, a reliable and valid measure of the intermittent repeated sprint agility performance. As this ability is required in all team sports, it is suggested that team sports coaches, fitness coaches and sports scientists consider this test in their training follow-up.